Digital Threads via Knowledge-Based Engineering Systems - Joe David; Eeva Jarvenpaa; Andrei Lobov (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2021)
Digitalization of manufacturing is led by the notion of a digital thread, a framework that allows for integrating authoritative and trustable data of a product throughout its lifecycle. Under the model-based enterprise (MBE) vision, digital three-dimensional (3D) model of a product serve as this authoritative source of information across the product lifecycle. A class of systems called knowledge-based engineering (KBE) systems represents the evolution of knowledge-based systems towards designing these models and this study presents a case for using such systems to realize the digital thread in a model-based enterprise. The paper proposes four directions and potential enabling technologies at the disposal of KBE systems for this purpose are identified. Further, a case-study that demonstrates such use of a KBE software to realize the digital thread for a manufacturing assembly process is presented.